Coexistence of blaNDM–5 and tet(X4) in international high-risk Escherichia coli clone ST648 of human origin in China - Shafiq, Muhammad; Zeng, Mi; Permana, Budi; Bilal, Hazrat; Huang, Jinhu; Yao, Fen; Algammal, Abdelazeem Mohamed; Li, Xin; Yuan, Yumeng; Jiao, Xiaoyang (Frontiers in Microbiology, 2022)
The emergence of pathogens conferring resistance to last-resort therapies like tigecycline, colistin, and carbapenems limiting the therapeutic options and raising concerns about the emergence of new "superbugs". The current study reports the first incident of a blaNDM-5 and tet(X4) co-harboring E. coli with resistance to carbapenem and tigecycline recovered as causative agent of a urinary tract infection in a 94-year-old patient. The E. coli strain ECCL209 carries multiple resistance genes (i.e., blaTEM-1B, blaNDM-5, blaCMY-2, aadA22, florR, erm(B), mph(A), erm(42), lnuG, qnrS1, and sul2), and exhibits resistance to almost all clinically used antibiotics. MLST analysis found that the strain belongs to ST648, considered as a worldwide high-risk pandemic clone. Moreover, multiple plasmid incompatibility types were detected, i.e., IncHI1A, IncHI1B, IncFII, IncFIA, IncFIB, IncQ1, Col, IncX4. Genetic analysis revealed that blaNDM-5 and tet(X4) genes were localized on two hybrid plasmids with multiple replicons. Continuous monitoring studies are suggested to quantify the antimicrobial resistance and assess the dissemination of such superbugs into a human health care setting.